Age as a modifier of the effects of sarcopenia on survival among colon cancer patients after surgery - Lin, Wen‐Li; Wu, Li‐Min; Huang, Wen‐Tsung; Guo, How‐Ran; Chen, Jyh‐Jou (Journal of surgical oncology, 2023)
BackgroundStudies have been conducted to evaluate whether sarcopenia is a predictor for survival in patients with colon cancer postsurgery, but findings have been inconsistent, and effects of age were seldom evaluated.MethodsWe recruited 133 patients with resectable colon cancer who underwent surgery between January 2014 and December 2017 at a teaching hospital to evaluate the effects of sarcopenia on survival, after adjusting for age and other potential predictors, including visceral adiposity (VA).ResultsPreoperative sarcopenia was associated with worse overall survival (OS: 62.3% vs. 83.8%, p = 0.04) and longer hospital stay (20.6 vs. 14.9 days, p < 0.01) while VA was not. Cox proportional hazards regressions showed that sarcopenia was associated with an adjusted hazard ratio (HR) of 2.91 (95% confidence interval [CI]: 1.08−7.86) after adjustment for other independent risk factors, but was not associated with disease free survival. In stratified analyses, we found that sarcopenia was an independent factor for worse OS (adjusted HR = 1.94; 95% CI: 1.11−3.38) among patients >70 years, but not among patients ≤70 years (HR = 0.48; 95% CI: 0.55−4.55).ConclusionsAge appeared to be a modifier of the effects of sarcopenia on OS among colon cancer patients postsurgery.